3-D numerical models of viscous flow applied to fold nappes and the Rawil depression in the Helvetic nappe system (western Switzerland). (May 2016) - von Tscharner, M.; Schmalholz, S.M.; Epard, J.-L.
Abstract: The Helvetic nappe system exhibits three-dimensional (3-D) features such as the lateral variation in geometry between the Morcles and Doldenhorn fold nappes or the Rawil depression. We perform 3-D finite element simulations of linear and power-law viscous flow to investigate fold nappe formation during shortening of a half graben with laterally varying thickness. 3-D ellipsoids and corresponding 2-D intersection ellipses are used to quantify finite strain. Fold nappes which formed above a thicker graben have (i) larger amplitudes, (ii) a less sheared and thinned overturned limb, and (iii) a larger thickness than fold nappes formed above a thinner graben. These results agree with observations for the Morcles and Doldenhorn nappes. We also perform 3-D simulations for a tectonic scenario suggested for the evolution of the Rawil depression. The basement is shortened and extended laterally and includes a graben which is oblique to the shortening direction and acts as mechanical weak zone. The graben causes laterally varying basement uplift generating a depression whose amplitude depends on the graben orientation and the stress exponent of basement and sediments. The axial plunge of the depression is smaller (approximately 10°) than the observed plunge (approximately 30°) indicating that additional processes are required to explain the geometry of the Rawil depression. Highlights: We model viscous fold nappe formation in 3-D with laterally varying geometry. We model 3-D deformation and uplift of basement with an oblique (weak) graben. We test hypotheses suggested for the Helvetic nappe system and the Rawil depression. We calculate and visualize finite strain ellipsoids and intersection ellipses. Differences between Morcles and Doldenhorn nappes are explained by 3-D model.